Cyclic AMP: a mitogenic signal for Swiss 3T3 cells. - Rozengurt, E (1981)
Addition of cholera toxin (100 ng/ml) to quiescent cultures of Swiss 3T3 cells acts synergistically with serum (2-4%), insulin, phorbol esters, epidermal growth factor, and fibroblast-derived growth factor to stimulate DNA synthesis. In the presence of insulin, cholera toxin caused a dose-dependent increase in cumulative [3H]thymidine incorporation into acid-insoluble material and in the intracellular cyclic AMP (cAMP) level. The dose--response curves for the two processes were similar. Furthermore, addition of 1-methyl-3-isobutylxanthine (15--500 microM) or of 4-(3-butoxy-4-methoxybenzyl)-2-imidazolidinone (5--100 microM), both of which are potent inhibitors of cyclic nucleotide phosphodiesterase which are potent inhibitors of cyclic nucleotide phosphodiesterase activity, stimulated DNA synthesis and increased cAMP levels in Swiss 3T3 cells. These compounds strikingly potentiated the effect of cholera toxin on DNA synthesis and on cAMP levels. When quiescent Swiss 3T3 cells were exposed to cholera toxin (100 ng/ml) and insulin at 10 micrograms/ml (4- to 7-fold increase in cAMP level) or to these agents and 1-methyl-3-isobutyl xanthine at 50 microM (35-fold increase in cAMP level), DNA synthesis began after a lag of 16 hr. These results indicate that cAMP acts as a mitogenic signal for Swiss 3T3 cells and differ from the widely held view that cyclic AMP inhibits the proliferation of fibroblast cells.